The use of public relations and social media by schools in the process of informing the public - Tane Dimovski (Institute of Communication Studies, 2022)
The Internet is a natural environment for the new generation. Children today do not learn how a computer is used, but use a computer when learning. Through the search engine, it is possible to find an answer to any question that someone might have. In other words, the Internet has penetrated all areas of human life. In the future, the computer will play an even greater role in people's lives. However, the chief institute in the direction of the educational system of young people remains to be the school. Today, public relations and social media are an integral part of the educational process, precisely in the part of the availability of information to the public. They represent an essential and firmly integrated relation in public policies in every field of interest. Their use in today's world, in an era of fast communication, has become part of our daily lives because they summarize public opinion. The schools managed to maximize this free internet space and use public relations and social media management techniques by placing photos, content, comments, videos, etc. i.e., sharing informative announcements for the public, which contributed to creating, establishing, and projecting the image of the educational institution. Thus, schools managed to bring their activities and information to the public and change the long-standing habit of non-compliance with public information.